2016
DOI: 10.18632/oncotarget.11759
|View full text |Cite
|
Sign up to set email alerts
|

On metabolic reprogramming and tumor biology: A comprehensive survey of metabolism in breast cancer

Abstract: Altered metabolism in tumor cells has been a focus of cancer research for as long as a century but has remained controversial and vague due to an inhomogeneous overall picture. Accumulating genomic, metabolomic, and lastly panomic data as well as bioenergetics studies of the past few years enable a more comprehensive, systems-biologic approach promoting deeper insight into tumor biology and challenging hitherto existing models of cancer bioenergetics. Presenting a compendium on breast cancer-specific metabolom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 181 publications
(197 reference statements)
0
54
0
Order By: Relevance
“…Positive aerobic glycolysis and subsequent metabolic reprogramming in cancer cells are collectively known as the Warburg effect (31). Various researchers have demonstrated the impact of the Warburg effect on the metabolite profiles of CSCs or CSC-like spheroids reconstructed from original breast, colorectal, hepatic and ovarian cancer PCs (32)(33)(34)(35)(36). Among the amino acids, aspartate, serine, glutamic acid and glutamine are assumed to be particularly good targets for cancer therapeutics in CSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Positive aerobic glycolysis and subsequent metabolic reprogramming in cancer cells are collectively known as the Warburg effect (31). Various researchers have demonstrated the impact of the Warburg effect on the metabolite profiles of CSCs or CSC-like spheroids reconstructed from original breast, colorectal, hepatic and ovarian cancer PCs (32)(33)(34)(35)(36). Among the amino acids, aspartate, serine, glutamic acid and glutamine are assumed to be particularly good targets for cancer therapeutics in CSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Despite huge differences between the two metabolic phenotypes, they seem to be reconciled with each other due to the complex metabolic plasticity and regulation. Moreover, the metabolic diversity of cancer tissue reflects rapidly adaptation to the drastic changes in nutrient environment [ 98 ].…”
Section: Introductionmentioning
confidence: 99%
“…A second hypothesis to explain these observations could be that cancer cells and their microenvironment consume lactate leading to its levels drop with growing tumor mass. Several facts do not support such a speculation: cancer cells themselves produce and excrete large amounts of lactate in their stroma where this metabolite plays subtle and complex roles favoring tumor progression [ 21 , 22 ]; Kallinowski F. et al showed that in human breast cancer xenografts in nude rats, lactate is released from tumors [ 23 ]; Kennedy KM. et al found that, in vitro , lactate can be metabolized by some but not all types of BC cells [ 24 ].…”
Section: Discussionmentioning
confidence: 99%